Rising Mesopores to Realize Direct Electrochemistry of Glucose Oxidase toward Highly Sensitive Detection of Glucose. (28th August 2019) - Liang, Taotao; Zou, Long; Guo, Xiaogang; Ma, Xiaoqing; Zhang, Chenke; Zou, Zhuo; Zhang, Yuhuan; Hu, Fangxin; Lu, Zhisong; Tang, Kanglai; Li, Chang Ming
Abstract: Direct electrochemistry, a direct electron transfer process between enzymes and electrode possesses, has important fundamental significance in bioelectrochemistry while offering very efficient electrocatalysis for enzyme‐based sensors. Herein, the pore structure of bacterial cellulose porous carbon nanofibers (BPCNFs) is tailored by controlled thermal carbonization. It is discovered that rising mesopores can realize a fast direct electrochemistry of glucose oxidase (GOx) for highly sensitive detection of glucose, achieving a sensitivity of 123.28 µA mmol L −1 cm −2 and a detection limit of 0.023 µmol L −1 . The enhancement mechanism for the mesopores is ascribed to the most adequate mesopores of BPCNF900, which offer size‐matched "nests" to trap GOx for intimate contacts with the conductive carbon nanofiber enabling fast direct electrochemistry. In addition, with the BPCNF900 sensing platform, the mechanisms for GOx‐direct‐electrochemistry‐catalyzed glucose oxidation and oxygen reduction are systematically investigated to further clarify the confusions of glucose sensing in air and N2 ‐saturated solutions. This work demonstrates fundamental insights for the direct electrochemistry enabled by rationally designing a pore structure matching the target proteins, thus possessing universal significance in protein‐based electrochemical devices while offering a facile route to fabricate a highly sensitive glucose sensor for practical clinic diagnosis. Abstract : Bacterial cellulose porous carbon nanofibers (BPCNF)900 with the most adequate mesopores offer size‐matched "nests" to trap glucose oxidase (GOx) for intimate contacts with the conductive carbon nanofiber enabling fast direct electrochemistry of GOx without any electron mediator. The glucose sensor fabricated by the BPCNF900 shows a fast direct electrochemistry of glucose oxidase to catalyze GOx for highly sensitive and selective sensors with a rapid response time.